2016
DOI: 10.1016/j.chom.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Integration of Stress Signals by Pathogenic Bacteria

Abstract: For pathogenic bacteria, the ability to sense and respond to environmental stresses encountered within the host is critically important, allowing them to adapt to changing conditions and express virulence genes appropriately. This review considers the diverse molecular mechanisms by which stress conditions are sensed by bacteria, how related signals are discriminated and how stress responses are integrated, highlighting recent studies in selected bacterial pathogens of clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…The ability of bacteria to modify gene expression levels in adaptation to external influences is key to many aspects of bacterial pathogenesis [ 1 ]. Two-component regulatory systems (TCS) are a major mechanism by which bacteria detect and respond to diverse environmental factors [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of bacteria to modify gene expression levels in adaptation to external influences is key to many aspects of bacterial pathogenesis [ 1 ]. Two-component regulatory systems (TCS) are a major mechanism by which bacteria detect and respond to diverse environmental factors [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A defining feature of bacterial pathogens is the ability to sense host metabolites and precisely coordinate the expression of multiple virulence factors (Fang, Frawley, Tapscott, & Vazquez‐Torres, ; Fang, Frawley, Tapscott, & Vazquez‐Torres, ; Finlay & Cossart, ; Olive & Sassetti, ). Bile is a well‐characterised host metabolite, biosynthesised from cholesterol by hepatocytes in the liver (Joyce & Gahan, ; Vitek & Haluzik, ).…”
Section: Introductionmentioning
confidence: 99%
“…The apo-SlyA spectrum is well dispersed (Figure 2), with ∼85% of the expected resonances observed. However, wide variation among individual resonances with respect to peak width and intensity may signify [1] weak non-specific interactions between SlyA dimers, [2] varying rates of exchange of amide protons with solvent, or [3] conformational exchange. Previous studies of MarR found that apo-MarR is also highly disordered (8), suggesting that the observed spectral characteristics of apo-SlyA can be ascribed to the presence of multiple conformational states in solution.…”
Section: Resultsmentioning
confidence: 99%